Magical secrets about thinking creatively : the art of etching and the truth of life - Brown, Kathan (San Francisco : Crown Point Press, 2006)
Crown Point Press's founder, Kathan Brown, presents thirteen "magical secrets"--Creative strategies exemplified by the different approaches to art-making taken by artists she has worked with. Sophisticated and yet straightforwardly explained, the magical secrets help the reader understand fundamental strategies such as how to creatively use the physicality of materials or how an artist may enter a mental state that encourages creative connections. Explanations of printmaking processes and reproductions of prints help to illuminate the secrets. An accompanying DVD features Brown's "Magical Secrets" lecture. Magical Secrets offers a deeper understanding of the creative impulses in us all
-- Cultivate Sensuality: Hard Ground Etching -- Intaglio -- Aquatint / Wayne Thiebaud -- Use a Lot of Time: Mezzotint / Chuck Close -- Get into the Flow: Drypoint / Richard Diebenkorn, Nathan Oliveira -- Have an Idea: Soft Ground Etching / Tom Marioni, Sol Lewitt, Hans Haacke -- Don't Know What You Want: Monotype -- Chine Colle -- Engraving / John Cage -- Know What You Don't Want / Robert Bechtle -- Stick Your Neck Out / Pat Steir -- Use Every Tool: Photogravure / Shahzia Sikander -- Use Every Source / Laura Owens -- Become Skillful / Fred Wilson -- Take Yourself Lightly / Peter Doig -- Go into the Ether / Richard Tuttle -- Own It / Dorothy Napangardi
Includes index
Keywords: Etching; Creative ability